Decision-making for national programs of community fluoride use - Horowitz HS (Blackwell Synergy, 2000)
Every community, region or country with a high or rising prevalence of dental caries should implement a caries-preventive program that automatically brings the benefits of systemic and topically applied fluoride to the entire population. The fluoridation of community water supplies or salt fulfills the requirements of providing safe, effective protection from dental caries at reasonable cost. The use of dietary fluoride supplements or fluoridated milk does not meet the requirements of a comprehensive national or community program because compliance is poor or only selected age groups are targeted. Water fluoridation is ideal for countries, regions or communities with many central water supplies or where salt production or distribution is not centralized or easy to control.